Exploring the Dilemmas, Challenges, and Opportunities of Adolescent Fatherhood: An Exploratory Case Study - Eugene Musiiwa Makhavhu M-Tech (Masters); Tendani Sara Ramukumba D-Tech (Doctoral); Mmajapi Elizabeth Masala-Chokwe D-Tech (Doctoral) (SAGE Publishing, 2023)
Teenage pregnancy is a significant concern for society, and the effect on education is immense. In South Africa, policies were thus introduced allowing pregnant school-going children to continue attending class until the baby's birth. However, research on adolescent pregnancy generally ignores teenage fathers and focuses mostly on teenage mothers. Parents of teenage girls are also encouraged to offer support to their children, but the same cannot be said about adolescent fathers. They confront numerous barriers in fulfilling their parenting roles. A qualitative exploratory study was conducted to explore adolescent fathers' dilemmas, challenges, and opportunities. Interviews were conducted to collect data from 5 adolescent fathers in 1 township in South Africa. Findings indicate that adolescent fathers face various challenges and experience fatherhood differently. The phenomenon's effects on education are immense and unavoidable, yet some opportunities accompany the fathering role. Adolescent fathers are exposed to several complex situations that impact their lives. To understand these, further research studies into adolescent fatherhood still need to be conducted, and reproductive health education efforts should equally be directed toward empowering boys to the same extent as girls.